Laser Treatment of Scars - Oliaei, Sepehr; Nelson, John Stuart; Fitzpatrick, Richard; Wong, Brian J.F. (Facial Plastic Surgery, 2012)
Recent advances in optical technologies have produced laser systems capable of optimizing the appearance of scars from various etiologies. Laser treatment can commence as early as the time of the initial injury and as late as several years after the injury. Optimal results can now be attained with minimal down time. Herein, we review several available optical technologies for treatment of surgical, traumatic, and inflammatory scars, based upon our clinical experience.
Keywords: laser; scar; revision; fractional; acne